Hubungan cara Pemberian Air Susu Ibu (ASI) terhadap Kejadian Diare pada Bayi 6-11 Bulan di Puskesmas Kota Cimahi Provinsi Jawa Barat - Suryamah, Yeni (stikes dharma husada bandung, 2019)
Diarrhea disease is still a public health problem in developing countries such as Indonesia because of morbidity and mortality which is still high. On Cimahi City in 2013 the incidence of diarrhea was on third place (10.69%) after acute respiratory infection and acute nasopharyngitis on patients age group 0 to less than one year. Number of less-one-year infants with diarrhea disease who came to the public health center in Cimahi City was 19.53% and the number of 1-4 years old toddlers was 13.41% in 2014.. Many factors play an important role against children under five's illness especially diarrhea which among its are breastfeeding (breast milk). Some ways of breastfeeding are by giving directly to the baby or give it indirectly through expressed breast milk. The purpose of this study was to determine the relationship between the way of breastfeeding and the incidence of diarrhea in infants 6-11 months in public health centers Cimahi City in 2015 before and after controlling for variables maternal education, maternal occupation, socio economic status, hygiene of food and drink, sex, age infant, complementary feeding, and nutritional status. The study design using case-control study in which cases were infants aged 6-11 months who come to the public health center and was diagnosed as a case of diarrhea while control is taken at the same public health center and in the same week and do not suffer from diarrhea or infants who visit for immunizations. Case control comparative is 1: 1 with 154 chosen samples from each group. Multivariate analysis using logistic regression. The survey results revealed significant correlation between expressed breast milk with the incidence of diarrhea in infants (p = 0.019). The expressed breast milk has a protective effect 0.546 times less protection against diarrhea compared with infants fed breast milk directly. While the not breast milk / formula milk is known that there are no significant relationship with the occurrence of diarrhea (p = 0.858). There was no significant relationship between how breastfeeding by the incidence of diarrhea in infants after the controlled variable hygiene of food and drinks with p value of 0.055 (95% CI 0.360-1.011) and 0.875 (95% CI 0.360-1.011). It is hoped that the department of health and public health centers can increase promotional efforts to expectant mothers and mothers of infants, especially on hygiene of food and drink for use by infants including handwashing, increased promotional efforts health on complementary feeding, and the need for socialization of giving expressed breast milk to the baby to support the movement of breastfeeding until the age of two years